Marketing ethics and the marketing mix: Managerial Issues - R. Abratt (South African Journal of Business Management, 1989)
Marketing, more so than any other business discipline, has been criticized by people for hurting consumers, society as a whole, and other business firms. Deceptive prices, high advertising and distribution costs, high-pressure selling and unsafe products are common complaints. This article reviews some of the Issues involved. It deals with marketing ethics and its problems and then discusses the role of ethics in the marketing mix. The article calls for marketers to adhere to ethical standards of conduct or face the consequences.
Keywords: 650